Problematika Stabilization Clauses dalam Kontrak Karya PT Freeport Indonesia Dan Kewajiban Membangun Smelter Pasca Putusan MK No 10/PUU-XII/2014 - Arifin Ma’ruf (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
This paper discusses the problems of stabilization clauses in the contract of work PT Freeport Indonesia and the obligation to build a smelter after the Constitutional Court Decision No. 10 / PUU-XII / 2014, which contracts the work done by the government of Indonesia and PT Freeport Mc Moran is basically a contract concessions the majority of shares are held by the company Freeport McMoran and based on the clause that called stabilization clauses, meaning that mining / consesions agreement that has been signed today by the Freeport McMoRan and the Indonesian government based on the positive law today and should not be changed arbitrarily by the parties to the agreement, and turn must pass through the negotiation process, it causes other problems seriously on the current conditions, on the other hand after the Constitutional Court decision of the Constitutional Court No. 10/PUU-XII / 2014, although there are pros and cons that are very visible in the trial will but ahirnya Constitutional Court rejected the applicant in its entirety, so that the article being tested remain valid and require every mining company to make semelter enabled to pengilahan and purification of the mines in the country, but the construction of the smelter by PT Freeport Indonesia until 2016 only 15 per cent , This shows the company's half-heartedness in carrying out the mandate of the Mining Law, that should begin in 2014 for holders of contracts of work had to be beroprasi.